Learner Satisfaction and Experience With a High-definition Telescopic Camera During Vaginal Procedures: A Randomized Controlled Trial. Issue 2 (February 2021) - Hobson, Deslyn T. G.; Meriwether, Kate V.; Gaskins, Jeremy T.; Uddin, M. Nazir; Stewart, J. Ryan; Gupta, Ankita S.; Francis, Sean L.
Abstract : Objective: The aim of this study was to compare learner satisfaction and experience with a table-mounted, projecting, high-definition telescopic camera system (VITOM) versus traditional learner observation during vaginal surgery. Methods: Medical student and resident learners were randomized to vaginal surgery observation with or without the use of VITOM. We collected data on learner characteristics and their experience with vaginal surgery. After the surgery, learners completed the faculty/preceptor and working environment domains of the Veterans Affairs Learner's Perceptions Survey (VA LPS). The primary outcome was learners who were "very satisfied" on the VA LPS faculty/preceptor domain. We queried their ability to observe the surgery and satisfaction with learning in the operating room using a 100-mm visual analog scale. Results: Ninety-two learners completed the study (n = 44 VITOM, n = 48 no VITOM). There was no significant difference between groups in the proportion of learners "very satisfied" on the VA LPS faculty/preceptor domain (93.2% VITOM vs 91.5% no VITOM; odds ratio, 1.27; 95% confidence interval, 0.20–9.19; P = 0.99). Learners in the VITOM group were more likely to report ability to see what the main surgeon was doing (93.2% VITOM vs 62.5% no VITOM; odds ratio, 8.02; 95% confidence interval, 2.07–46.32; P < 0.01). Using the visual analog scale, learners in the VITOM group reported higher satisfaction with learning in the operating room (median, 96 [interquartile range, 89–100] VITOM vs median, 80 [interquartile range, 57–98] no VITOM; P < 0.01). Conclusion: The use of a table-mounted, projecting, telescopic camera system during vaginal surgery showed no difference in learner satisfaction on validated questionnaires but resulted in improved experience and visualization. Abstract : Supplemental digital content is available in the text.